Arthroscopic treatment for nonunion of the scaphoid - Haugstvedt, Jan Ragnar; Wong, Clara Wing-yee (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2020)
Scaphoid nonunion has traditionally been treated by open surgery where the pseudarthrosis has been cleaned while either a structural wedged bone graft, or chips of cancellous bone has been used to fill the defect. K-wires or a screw has been used to stabilize the bone. Using the arthroscopic technique for treatment of nonunion of the scaphoid gives us small exposure to the joint, however with an excellent view of the bones, the articular surfaces and the intraarticular ligaments. The results from arthroscopic treatment for scaphoid nonunion with bone grafting using chips of cancellous bone are as good as from the open technique. The arthroscopic treatment, though, helps us to diagnose and treat concomitant lesions. There is less damage of blood supply, nerves and capsule, which might lead to a faster recovery and rehabilitation. The technique will be described and discussed.
Keywords: Scaphoid nonunion; arthroscopy; arthroscopic treatment